Evaluating 56-Day Strength as a Basis for Design in Climate-Reduced Concrete - Sernekvist, Saga (My University, 2026)
The construction sector is responsible for a significant share of global greenhouse gas emissions, primarily due to the production of Portland cement. To address this, supplementary cementitious materials such as Ground Granulated Blast-furnace Slag (GGBS) are increasingly used as partial cement replacements in climate-reduced concrete. While these materials reduce embodied carbon, they also alter the strength development characteristics of the concrete, most notably by slowing early-age strength gain while enabling continued strength development beyond 28 days. Current structural design practice evaluates concrete compressive strength at 28 days, which is the basis for concrete classification under Eurocode 2. For slag-containing concretes, this approach neglects a potentially significant additional strength gain at later ages. This thesis investigates whether 56-day compressive strength can serve as a viable basis for structural design, and evaluates the practical implications for strength development, reinforcement demand, and embodied carbon. Laboratory data from concrete mixes with GGBS contents between 26% and 51% were analysed, showing relative strength increases between 28 and 56 days ranging from approximately 3% to 13%. A numerical strength development model was calibrated using in-situ temperature measurements from six floor slabs in a residential building constructed with 32% GGBS concrete. The calibrated model was applied to three structural elements, a filigree floor slab, a ground slab, and a basement external wall, using spring temperature data from Gothenburg as boundary conditions. The results show that C28/35 concrete with 32% GGBS can approach or reach the 37 MPa cube strength associated with C30/37, but that all investigated elements required considerably longer than 56 days under the simulated conditions, with approximately 80 days being a more representative figure for this specific case. The reinforcement demand was governed by ULS bending for the floor slab, where concrete strength class has only a minor influence, and by crack width control for the ground slab and basement wall, where the difference between C28/35 and C30/37 amounts to 22 mm²/m. A reduction in strength class from C30/37 to C28/35 is estimated to reduce total CO2-equivalent emissions by approximately 6% at Level 3 and 4% at Level 4 climate performance. The study concludes that later-age strength development in GGBS concrete offers measurable potential for more efficient structural design, but that careful consideration of early-age behaviour, curing conditions, and production constraints is required before such an approach can be applied in practice.
Keywords: Climate-reduced concrete, GGBS, Compressive strength, 56-day strength, Structural design, Maturity method, Embodied carbon